언어재활사의 몸짓언어중재 실태와 ‘표준 몸짓언어 체계’ 개발의 필요성 조사연구 - 이효주(Hyo Joo Lee); 서창원(Chang Won Seo) (언어치료연구, 2017)
목적: 본 연구의 목적은 언어재활사의 몸짓언어중재 실태를 조사하고, ‘표준 몸짓언어 체계’ 개발의 필요성과요구사항 등을 조사하는 것이었다. 방법: 선행연구를 참고하여 언어재활사의 기본정보 및 근무 정보, 중재 대상자의 특성 및 몸짓을 사용한 언어중재의 실태, 표준화된 몸짓언어 체계 개발의 필요성 조사의 세 영역으로나눈 설문지를 구성하였다. 전국 언어재활사에게 이메일을 통해 배포하였으며, 총 113명에 대한 응답 결과를회수하였다. 회수된 설문지에 대하여 빈도와 백분율을 분석하였다. 결과: 첫째, 언어중재를 실시하는 대상자가 가진 장애의 종류는 자폐스펙트럼장애와 지적장애가 가장 많았으며, 대상자들이 보이는 주요한 문제는 표현 및 수용언어문제였다. 또한 대부분의 언어재활사가 구어 산출이 제한적인 대상자를 중재해본 경험이 있다고 하였다. 둘째, 구어 산출이 제한적인 대상자에게 주로 사용한 보완적인 의사소통 수단은 몸짓(제스처)가가장 높은 빈도를 차지하였고, 몸짓 중재를 실시할 때 중재자가 직접 고안한 체계를 사용하는 경우가 가장 많았다. 셋째, ‘표준 몸짓언어 체계’의 개발이 필요한지에 대하여 ‘그렇다’고 응답한 언어재활사는 95.6%로 매우 높은 비율을 보였다. 결론: 본 연구의 결과를 통해 현재 임상 현장에서 실시되고 있는 몸짓언어중재의 실태를 확인할 수 있었다. 실제 언어재활 현장에서 제한적인 구어 능력으로 인해 보완대체 의사소통을 필요로하는 대상자들의 비율이 많았고, 이들을 대상으로 주로 몸짓을 사용한 중재가 진행되고 있었다. 구어가 제한적인 대상자를 대상으로 더불어 언어재활사들에게 유용한 ‘표준 몸짓언어 체계’의 개발이 필요하다는 것과 체계의 개발과 관련한 요구사항 등을 제안하였다. Purpose: The present study aimed to investigate body language intervention by speech language pathologists (SLP) and the necessity of developing a 'body language system.' Methods: Three areas were measured via questionnaire: SLPs' basic information and working information, the characteristics of intervention subjects, including the actual condition of language intervention using gestures (body language), and the necessity of developing a 'standardized body language system.' Questionnaires were emailed to SLPs and 113 responses were collected. The frequency and percentage of the collected questionnaires were analyzed. Results: First, autistic spectrum disorder and intellectual disability were the most common disabilities of the subjects who had language intervention. The main problem with subjects was the problem of expressive and receptive language. In addition, 84.1% of SLPs had mediated subjects with limited use of spoken language. Second, gestures were the most frequently used complementary means of communication used for subjects with limited use of spoken language; when using gesture mediation, most SLPs used gesture intervention systems designed by themselves Third, the rate of SLPs who answered 'yes' to the need for development of a 'standard gesture language system' was 95.6%. Conclusions: The results of this study confirmed the actual condition of body language intervention in the clinical field. In the actual language rehabilitation field, the number of subjects with limited spoken ability requiring AAC was high and intervention using gestures was mainly conducted for these subjects. In addition, we suggested the development of a 'standard body language system' which could be useful for SLPs, and the requirements for the development of such a system. KCI Citation Count: 4